Excess body fat negatively affects bone mass in adolescents - Mosca, Luciana Nunes [UNESP]; Goldberg, Tamara Beres Lederer [UNESP]; Silva, Valeria Nobrega da [UNESP]; Silva, Carla Cristiane da; Kurokawa, Cilmery Suemi [UNESP]; Rizzo, Anapaula da Conceição Bisi [UNESP]; Corrente, José Eduardo [UNESP] (Elsevier B.V., 2014)
Objective: The aim of this study was to investigate the effects of excess body fat on bone mass in overweight, obese, and extremely obese adolescents.Methods: This study included 377 adolescents of both sexes, ages 10 to 19 y. Weight, height, body mass index (BMI), bone age, bone mineral content (BMC), and bone mineral density (BMD) were obtained by dual-energy x-ray absorptiometry. The results were adjusted for chronological age and bone age. Comparisons according to nutritional classification were performed by analysis of variance, followed by Tukey test. Linear regression models were used to explain the variation in BMD and BMC in the L1-L4 lumbar spinal region, proximal femur, and whole body in relation to BMI, lean mass, fat mass (FM), and body fat percentage (BF%), considering P < 0.05.Results: For all nutritional groups, average bone age was higher than chronological age. In both sexes, weight and BMI values increased from eutrophic to extremely obese groups, except for BMD and BMC, which did not differ among male adolescents, and were smaller in extremely obese than in obese female adolescents (P < 0.01). Significant differences were observed for FM and BF% values among all nutritional groups (P < 0.01). Positive, moderate to strong correlations were detected between BMD and BMC for BMI, lean mass, and FM. A negative and moderate correlation was found between BMC and BF%, and between BMD and BF% at all bone sites analyzed in males and between BF% and spine and femur BMD, in females.Conclusion: The results reveal a negative effect of BF% on bone mass in males and indicate that the higher the BF% among overweight adolescents, the lower the BMD and BMC values. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Adolescents; Bone mineral content; Bone mineral density; Obesity; Osteoporosis; Overweight